Differences in the Improvement of Statistical Reasoning Ability Based on Students' Self-Regulated Learning Level in Online Learning Using LMS - Jauhari, Afifah Latip Rasyid; Herman, Tatang; Juandi, Dadang; Negara, Habibi Ratu Perwira (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
In the literature, studies on technology-supported learning, especially using LMS, have been widely carried out during a pandemic. However, little is known about LMS, which is interesting and helps to develop students' statistical reasoning abilities for online learning by considering the students' Self-Regulated Learning (SRL) levels (High, medium and low). This study aims to examine and analyze the differences in statistical reasoning abilities of students who study using LMS in terms of SRL levels (high, medium and low). This study uses a quantitative method with the type of One-group pre-test post-test design. What took sampled randomly at the University of Pasundan Bandung, totalling 54 third-level students of Pasundan University Bandung, Indonesia. Research data related to statistical reasoning abilities were collected through a test consisting of six questions. In contrast, SRL level data were collected using a questionnaire consisting of 46 question items. Paired t-test and One-way ANOVA analysis were applied to answer the research hypothesis. The results of the study concluded that students studying with LMS with High SRL obtained a higher increase in statistical reasoning ability than students studying with LMS with Medium and low SRL categories, with the criteria for improvement in the three categories being in the high and medium improvement categories. Research findings related to learning using LMS can be used as an alternative learning model in online learning situations.